Recurrent pneumothorax following chest tube removal in thoracic stab wounds: a comparative study between end inspiratory versus end expiratory removal techniques at a major trauma centre in South Africa. Issue 4 (15th March 2021) - Kong, Victor; Cheung, Cynthia; Rajaretnam, Nigel; Sarvepalli, Rohit; Weale, Ross; Varghese, Chris; Xu, William; Clarke, Damian L.
Abstract: Background: Tube thoracostomy (TT) insertion is a commonly performed procedure in trauma that is standardised, but the optimal removal technique based on the timing in relation to the respiratory cycle remains controversial. Methods: A prospective study was undertaken at a major trauma centre in South Africa over a 4‐year period from January 2010 to December 2013, and included all patients with pneumothorax secondary to thoracic stab wounds. TTs were removed by either end of inspiration technique (EIT) or end of expiration (EET) technique and the rate of recurrent pneumothorax (RPTX) following removal was compared. We hypothesized that there is no difference in the rate of RPTX between the end inspiratory (EI) and end expiratory (EE) removal technique. Results: A total 347 patients were included. Of the 184 TTs removed by EIT, there were 17 (9%) RPTXs. Of the 163 with EET, there were 11 RPTXs (7%), (9% versus 7%, chi‐squared, P = 0.395). Of the total 28 (9%) patients with RPTXs following removal of chest tubes, two (7%) required reinsertion of chest tube (0.5% (1/184) in EIT and 0.6% (1/163) in EET, P = 0.747). Conclusions: Timing of TT removal in relation to the respiratory cycle does not appear to influence the incidence of RPTX in patients with thoracic stab wounds. Technique of removal may well be a more important consideration and more attention must be focused on refining the optimal technique. Abstract : Recurrent pneumothorax following chest tube removal ‐ end expiratory vs end inspiratory removal technique This is a retrospective study that interrogated the rate of recurrent pneumothorax following tube thoracostomy removal between the end of inspiration versus the end of expiration removal techinques.